Censorship detected in BD (Bangladesh) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Bangladesh. Data sourced from OONI.
Censorship Incident ID: BD-2026-0485. Severity: critical. Confidence: 77%